2005
DOI: 10.1111/j.1523-1755.2005.00486.x
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive nephropathy: Insights from genetically engineered animals

Abstract: Congenital obstructive nephropathy is the primary cause for end-stage renal disease (ESRD) in children. An increasingly used animal model of obstructive nephropathy is unilateral ureteral obstruction (UUO). This model mimics, in an accelerated manner, the different stages of obstructive nephropathy leading to tubulointerstitial fibrosis: cellular infiltration, tubular proliferation and apoptosis, epithelial-mesenchymal transition (EMT), (myo)fibroblast accumulation, increased extracellular matrix (ECM) deposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
194
1
8

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(210 citation statements)
references
References 94 publications
7
194
1
8
Order By: Relevance
“…43,50 A number of studies have revealed major pathways leading to the development of renal fibrosis after UUO surgery: the initial event is interstitial infiltration of macrophages that produce cytokines responsible for fibroblast proliferation and activation. After UUO operation, macrophages infiltrate the tubulointerstitial space from blood vessels and become a major source of cytokines, such as TGF-␤.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…43,50 A number of studies have revealed major pathways leading to the development of renal fibrosis after UUO surgery: the initial event is interstitial infiltration of macrophages that produce cytokines responsible for fibroblast proliferation and activation. After UUO operation, macrophages infiltrate the tubulointerstitial space from blood vessels and become a major source of cytokines, such as TGF-␤.…”
Section: Discussionmentioning
confidence: 99%
“…42,43 Both Bsg ϩ/ϩ and Bsg Ϫ/Ϫ mice exhibited only slight macrophage infiltration at day 3 (Figure 2A). Macrophage infiltration into the interstitium became prominent at day 7, and increased more at day 14 ( Figure 2, A and B).…”
Section: Macrophage Infiltration Is Lower In Bsg ϫ/ϫ Micementioning
confidence: 99%
“…24 At present, one of the most important molecular mechanism of renal fibrosis in this model is increase of TGF-b. [23][24][25] Earlier studies have shown that macrophage/monocyte infiltration occurred in the kidney 4 h after acute ureteral obstruction and its peak response occurred at 24 h after UUO and stabilized thereafter. 26 Another study also showed a highly significant correlation between the increasing number of interstitial macrophage/monocyte and the cortical TGF-b mRNA levels.…”
Section: Discussionmentioning
confidence: 99%
“…Given that collagen accumulation is responsible for renal fibrosis, 22 the renal fibrosis in UUO can be explained, at least in part, by the enhancing of the TGF-b/collagen pathway. 23 A great deal of investigation has been conducted to understand the cellular and molecular mechanisms of renal fibrosis in this model. 24 At present, one of the most important molecular mechanism of renal fibrosis in this model is increase of TGF-b.…”
Section: Discussionmentioning
confidence: 99%
“…These animals have shown the complexity of apoptosis and tubulointerstitial fibrosis development involving a large number of closely related molecules functionally. In addition, the recent development of mechanical stretch in cultured epithelial cells that mimics renal tubular distention has led to the discovery of unexpected and contradictory roles of principal apoptosis modulating factors (Bascands and Schanstra 2005).…”
Section: Introductionmentioning
confidence: 99%